Efficacy and safety of traditional Chinese medicines combined with conventional Western medicines in the treatment of type 2 diabetes mellitus: a network meta-analysis of randomized controlled trials - Ma, Kaile; Zhou, Lijuan; Zhang, Yanjiao; Zhao, Jingyi; Yao, Chensi; Tian, Chuanxi; Li, Min (Frontiers in Endocrinology, 2023)
Aims/hypothesis Through a comprehensive analysis of the clinical randomized controlled trials of traditional Chinese medicine (TCM) combined with conventional western medicine (CWM) in treating type 2 diabetes(T2DM) in the past ten years, the clinical efficacy and safety of different TCMs combined with CWM were explored. This study aimed to provide specific suggestions for clinical guidance on treating T2DM. Methods A literature search was conducted in CNKI, WanFang, VIP, CBM, PubMed, Embase, and Web of Science. The search time was limited from 2010 to the present time. The literature type was a controlled clinical trial study of TCM combined with CWM intervention in treating T2DM. The outcome indices of the efficacy evaluation included fasting blood glucose (FBG), 2-hour postprandial blood glucose (2hPG), glycosylated hemoglobin (HbA1c), adverse reactions, and clinical efficacy. Stata 15 and RevMan 5.4 software were used to conduct a network meta-analysis and a traditional meta-analysis. Results The results showed that shenqi jiangtang granule combined with sulfonylurea, shenqi jiangtang granules combined with metformin and jinlida granules combined with insulin had significant effects on reductions in FBG, 2hPG and clinical efficacy compared with western medicines alone, which included fasting blood glucose [MD=-2.17, 95%CI=(-2.50, -1.85)], blood sugar at 2 hours after a meal [MD=-1.94, 95%CI=(-2.23, -1.65)], and clinical curative effect [OR= 1.73, 95%CI=(0.59, 2.87)]. Conclusions TCM combined with CWM has a very significant effect on treating T2DM compared with CWM alone. According to the network meta-analysis, the best intervention measures of different TCMs for different outcome indicators were obtained.